"Triple hit" lymphomas: A retrospective cytology case series of an uncommon high grade B‐cell malignancy with C‐MYC, BCL‐2 and BCL‐6 rearrangements. Issue 9 (25th July 2018) - Eldessouki, Tarek; Hanley, Kelly; Hamadeh, Fatima; Oshilaja, Olaronke O.; Sturgis, Charles D.
Abstract : The Revised fourth Edition World Health Organization (WHO) Classification of Tumors of Hematopoietic and Lymphoid Tissues suggests novel categories, including "high grade B‐cell lymphoma with MYC and BCL2 and BCL6 gene rearrangements." These diseases are known colloquially as "double hit" and "triple hit" lymphomas. The "first‐hit" in these cases is the harboring of a MYC rearrangement. Concurrent derangements of BCL2 and BCL6 can be the "second‐hit" or "third‐hit." To our knowledge, this is the first report of "triple‐hit" lymphomas in cytology specimens. The files of the Cleveland Clinic (January 2007 through December 2017) were searched for all "triple hit" lymphomas. Four cases met inclusion criteria (cytology slides in files and histologically confirmed "triple hit" lymphoma). All slides were reviewed. The mean age was 65 years, with a male predominance. All patients presented at advanced stage and showed progressive disease despite therapy. FISH studies (histologic sections) confirmed translocations of MYC (8q24), BCL2 (18q21) and BCL6 (3q27) in all patients. All cases were characterized by high cellularity, dispersed cells, presence of stripped nuclei, lymphoglandular bodies, apoptotic bodies, cytomegaly, nucleomegaly, nuclear envelope irregularities, macronucleoli (most often single), recognizable mitoses and presence of cytoplasmic vacuoles (variable). The WHO recommends that all large B‐cell lymphomas be investigated using cytogenetic or molecular techniques. Concurrent inhibition of MYC and BCL2 is a potentially effective treatment strategy for triple hit lymphomas, and an expanding literature exists regarding predictive biomarkers and therapeutic regimens. It is our intention to raise awareness of this uncommon mature B‐cell neoplasm within the cytodiagnostic community.